EXAMPLES OF LESSON PLANS FOR TEACHING ENGLISH IN MIDDLE SCHOOL (GRADES 6-9) - da Silva, Rosiane Pereira (Seven Editora, 2026)
This chapter presents practical examples of lesson plans for teaching English in middle school (grades 6-9), addressing different grammatical content, linguistic skills, and methodological strategies aimed at developing student learning. The lesson plans include objectives, methodologies, procedures, forms of assessment, and teaching resources, offering pedagogical support for English language teachers. Initially, the plans emphasize the development of the four linguistic skills—reading, writing, speaking, and listening comprehension—through contextualized, dynamic, and interactive activities. The chapter also values ​​active methodologies, using reading, dramatizations, games, group dynamics, bingo, text comprehension exercises, and oral activities to stimulate student participation and expand vocabulary in English. Another relevant aspect is the concern with continuous and formative assessments, carried out through observation of participation, oral and written performance, classroom interaction, and problem-solving exercises. In summary, this chapter demonstrates the importance of pedagogical planning in English language teaching, highlighting practices that make classes more motivating, participatory, and meaningful for middle school students.